Inhibitors of tyrosine kinases and phosphatases as a tool for the investigation of microtubule role in plant cold response - Sheremet, Ya.A.; Yemets, A.I.; Blume, Ya.B. (Цитология и генетика, 2012)
Tyrosine phosphorylation plays a vital role in the variety of signal transduction pathways in eukaryotic cells, however its role and relevance in plants are still largely unknown. To investigate the functional role of tubulin tyrosine phosphorylation in plant cells the interplay between the effects of tyrosine kinases (herbimycin A) as well as tyrosine phosphatases (sodium orthovanadate) inhibitors on microtubules sensitivity to cold in A. thaliana root cells were studied. Since it was found that inhibition of tyrosine kinases significantly increased the microtubules sensitivity to cold, while inhibition of tyrosine phophatases enhanced their cold-resistance, we suggest an existence of certain functional interaction between the phosphorylation on tyrosine residues and sensitivity of cortical microtubules to low temperatures.